Virtual Social Labs – Requirements and Challenges for Effective Team Collaboration - Maria Schrammel; ilse Marschalek (Journal of Responsible Technology)
In response to the challenges posed by the complex field of food safety, the FOODSAFETY4EU project established four social labs conducting multi-actor co-creation processes. These labs served as platforms for developing and piloting innovative ideas aimed at addressing these challenges. Due to COVID-19 pandemic, the lab process, typically held in-person, had to be converted to the virtual space. This means that all workshops, meetings, and collaboration processes and pilot activities solely took place online. This resulted in the novel situation of teams collaborating virtually throughout the entire social lab processes. Virtual collaborations were already on the rise before the pandemic, evidenced by an increase in virtual meetings and workshops. This study examines the requirements and challenges for effective team collaboration in virtual social lab processes. It investigates virtual collaboration, team dynamics, and the use of online tools. Findings reveal advantages such as increased participation, but also drawbacks including technical issues and role accountability. Despite challenges, all four virtual social labs finally succeeded in engaging diverse stakeholders and achieving significant outcomes addressing food safety challenges.